THE RECONSTRUCTION OF THE ROLE OF ISLAM IN INDONESIA AS A PROPETHIC RELIGION - Naupal, Naupal (Al-Ulum, 2014)
After the end of Soehartoâs regime, in 52Â  districts produced 78 regulations (perda) influenced Â by sharia to purify Islam from secular institutions. Because of that, Islam in Indonesia now is criticized as having a tendency to be close to status quo, and resulting so many problems, such as being injustice and dehumanize. Islam as a prophetic religion, as a religion not only for faith to Allah, isÂ  also a religion that liberating people from violence and injustice, as Prophet MuhammadÂ  brought it. This academic writing , using the hermeneuticmethodÂ  fromPaul Ricoeur, analizes the situation, by proposing three ways outthrough the theory of critical ideology,Â  andÂ  the deconstruction, andÂ  offering to accept plurality, to overcome the problems of complicated situation. Propethic religion might be the proper solution for the problems of Islam in Indonesia than priestly/institutional religion, in order to acheive the better Indonesian society, by practising tolerance, openess in mind, egaliter and democatic.Â ----------Setelah berakhirnya Rezim Suharto 52 wilayah di Indonesia membuat 78 Perda yang menginginkan pelaksanaan Islam secara kaffah. Oleh karena itu Islam di IndonesiaÂ  dikritik sebagai agama yang cenderung berada dalam status quo dan menyebabkan banyak masalah, seperti ketidakadilan dan tidak berperikemanusian. Islam sebagai sebuah agama kenabian tidak hanya berbicara tentang ketaatan kepada Allah, tetapi juga membahas tentang pembebasan manusia dari kekerasan dan ketidakadilan. Tulisan ini menggunakan metode Hermeunetik dari Paul Ricoeur Â yang menganalisis dengan mengajukan tiga teori yaitu kritik ideologi, dekonstruksi dan pluralism. Tulisan ini berusaha mengkaji peran Islam sebagai agama kenabian di Indonesia yang menci-citakan terwujudnya masyarakat Indonesia yang ideal, masyarakat toleran terbuka dan demokratis.